What Do Monkey Calls Mean?. Issue 12 (December 2016) - Schlenker, Philippe; Chemla, Emmanuel; Zuberbühler, Klaus
Abstract : A field of primate linguistics is gradually emerging. It combines general questions and tools from theoretical linguistics with rich data gathered in experimental primatology. Analyses of several monkey systems have uncovered very simple morphological and syntactic rules and have led to the development of a primate semantics that asks new questions about the division of semantic labor between the literal meaning of monkey calls, additional mechanisms of pragmatic enrichment, and the environmental context. We show that comparative studies across species may validate this program and may in some cases help in reconstructing the evolution of monkey communication over millions of years. Trends: Data gathered in field experiments provide detailed information about the form and function of monkey calls, especially the situations that trigger them and the information that conspecifics derive from them. While monkey calls differ radically from human language, their form and meaning can be illuminated using general tools from formal linguistics (morphology, syntax, semantics). Meaning studies should explain how monkey calls can encode information, thanks in particular to three components: the literal meaning of calls; knowledge of the environmental context; and some rules of competition among calls according to which more informative calls are normally preferred to less specific ones. Evolutionary connections between monkey calls and human language are unclear, but within monkey species the evolutionary history of calls can sometimes be traced over millions of years.